The Effect of Company Ownership Structure, Profit Rate and Company Risk on Intellectual Capital Performance (Study on Banking Companies Listed on The Indonesia Stock Exchange in 2017 - 2019) - Ria Lestari Pangastuti (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to determine the effect of managerial ownership structure, institutional ownership structure, profit level, and company risk on the significance of intellectual capital performance. This type of research is quantitative research where populations or samples are analyzed to test hypotheses. The population in this study is banking companies listed on the Indonesia Stock Exchange in 2017 - 2019. The method used is purposive sampling method, the sample obtained is 41 companies. The type of data used is secondary data where the data is processed from publication data. The results of this study indicate that managerial ownership structure has no significant effect on intellectual capital performance, institutional ownership structure has a significant effect on intellectual capital performance, profit level has no significant effect on intellectual capital performance, and company risk has no significant effect on intellectual capital performance.